A New Type II Half Logistic-G family of Distributions with Properties, Regression Models, System Reliability and Applications - Altun, Emrah; Alizadeh, Morad; Yousof, Haitham M.; Rasekhi, Mahdi; Hamedani, G. G. (Prairie View A & M Univ, Dept Mathematics, 2021)
This study proposes a new family of distributions based on the half logistic distribution. With the new family, the baseline distributions gain flexibility through additional shape parameters. The important statistical properties of the proposed family are derived. A new generalization of the Weibull distribution is used to introduce a location-scale regression model for the censored response variable. The utility of the introduced models is demonstrated in survival analysis and estimation of the system reliability. Three data sets are analyzed. According to the empirical results, it is observed that the proposed family gives better results than other existing models.
Keywords: Half Logistic-G Family; Incomplete Moment; Regression; Survival; Reliability; Simulation; Estimation